Morphological Variations of Nepenthes mirabilis (Lour.) Druce in the Peat Swamp Habitat - Singgih Tri Wardana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Nepenthes mirabilis is a type of lowland Nepenthes. Nepenthes mirabilis has morphological variations in size and color in its natural habitat. This study was conducted with the aim to determine the morphological variations of Nepenthes mirabilis in peat swamp habitat including stems, leaves and pitchers. This research was carried out in Pulu Beruang Village, Tulung Selapan District, Ogan Komering Ilir, South Sumatera. The research method used exploration method. Determination of the observation sample using a random plot method selected by purposive sampling. The parameters observed in this study were the morphological characteristics of Nepenthes mirabilis stems, leaves and sacs as well as environmental factors. Research results, Nepenthes mirabilis has a round stem shape (teres), red and green in color. The leaves are lanceolate, stalked, the edges of the leaves are flat and smooth, the upper surface of the leaves is green or reddish. Waist-shaped pouch, yellowish green in color with red striated and green with red spots.